Feminisation of the Labour Process in the Communication Industry: The Case of the Telephone Operators, 1876-1904. - Martin, Michèle (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1988)
Abstract This article uses concepts coming from studies of the feminization of different occupations to investigate how the occupation of telephone operator came to be a female job ghetto. Its main theme is that the feminization of operating was central to the rapid growth of the telephone industry in the late nineteenth and early twentieth centuries. Contrary to general findings in the literature on feminization, the study suggests that labelling the operator's occupation as a female job increased, rather than reduced, its social status, although it did not improve its wages. It also indicates that whereas the job definition changed to suit female characteristics, its actual performance continued to involve commonly recognised male features to which the female operators had to adapt.